How Populism Affects Bioethics - Ortiz Millán, Gustavo (Cambridge quarterly of healthcare ethics, 2025)
This article aims at raising awareness about the intersection of populism and bioethics. It argues that illiberal forms of populism may have negative consequences on the evolution of bioethics as a discipline and on its practical objectives. It identifies at least seven potential negative effects: (1) The rise of populist leaders fosters "epistemological populism," devaluing the expert and scientific perspectives on which bioethics is usually based, potentially steering policies away from evidence-based foundations. (2) The impact of "moral populism" is evident in legislative prioritization of the "morality of common people," often solicited through popular consultations on issues like abortion, drug legalization, or LGBT issues. (3) Populist distrust in autonomous governmental agencies and advisory bodies, including national bioethics commissions, can compromise expert advice, challenging both their authority and decisions. (4) Populists may erode transparency by undermining institutions responsible for it, hindering access to vital information for bioethical research. (5) "Medical populism" creates adversarial dynamics, prompting politicians to make simplistic healthcare policy decisions based on political rather than informed criteria, adversely affecting vulnerable populations. (6) Radical-right populist parties’ "welfare chauvinism" may shape healthcare policies, impacting service access and resource allocation, disproportionately affecting vulnerable groups such as migrants, but indirectly affecting the rest of the population. (7) Nationalist sentiments associated with populism may obstruct international collaborations, posing challenges for global bioethics that seeks to address ethical concerns beyond national borders. In summary, these dynamics raise significant bioethical concerns encompassing evidence-based decision-making, transparency, healthcare equity, and global collaboration. How bioethicists may respond to these challenges is discussed.